A survey on construction cost comparison between conventional and industrialised building system for housing project - Md. Rahim, Mohd Syazwan; Haron, Nuzul Azam; Hassim, Salihudin; Abdul Kadir, Mohd Razali (Institution of Surveyors Malaysia, 2006)
Malaysian construction industry is currently undergoing a transitional change from an industry, which is employing conventional technology to a more systematic and mechanized type of system. This new system is well known as Industrialised Building System (IBS). The new method of construction can increase productivity and quality of work through the use of better construction machinery, equipment, materials and project planning. This study becomes very necessary information on the construction cost comparison between the conventional and industrialised building system in the Malaysian construction industry. Data was collected by using mail questionnaire represents suppliers, developers, consultancies and also contractors.